2022
DOI: 10.48550/arxiv.2201.04433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accretion mode versus radio morphology in the LOFAR Deep Fields

B. Mingo,
J. H. Croston,
P. N. Best
et al.

Abstract: Radio-loud active galaxies have two accretion modes [radiatively inefficient (RI) and radiatively efficient (RE)], with distinct optical and infrared signatures, and two jet dynamical behaviours, which in arcsec-to arcmin-resolution radio surveys manifest primarily as centre-or edge-brightened structures [Fanaroff-Riley (FR) class I and II]. The nature of the relationship between accretion mode and radio morphology (FR class) has been the subject of long debate. We present a comprehensive investigation of this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 141 publications
(246 reference statements)
2
0
0
Order By: Relevance
“…8. Recent work by Mingo et al (2022) found a tail of LERGs with high sSFRs based on a study of the resolved radio-loud AGN within LoTSS-Deep; this is consistent with our study that finds the existence of a significant population of LERGs hosted by star-forming galaxies.…”
Section: Prevalence Of Lergs In Star-forming and Quiescent Galaxiessupporting
confidence: 93%
“…8. Recent work by Mingo et al (2022) found a tail of LERGs with high sSFRs based on a study of the resolved radio-loud AGN within LoTSS-Deep; this is consistent with our study that finds the existence of a significant population of LERGs hosted by star-forming galaxies.…”
Section: Prevalence Of Lergs In Star-forming and Quiescent Galaxiessupporting
confidence: 93%
“…While our sample mainly consists of intermediate disc and star-forming disc galaxies, the sample of O'Sullivan et al ( 2015) is dominated by spheroidal ones. Making the same comparison with the faint total power radio sky at longer wavelengths shows a distribution very similar to ours (Mingo et al 2022). The main difference arises in the flux range that the different samples cover.…”
Section: Discussionsupporting
confidence: 71%